Use of morphogenetic protein associated with xenogeneic graft for atrophic maxilla reconstruction: case report - Magalhães, Gustavo Henrique Melo; Rocha, Nelson Studart; Araújo, Fábio Andrey da Costa; Santana, Bruno de Macedo; Landim, Fabricio Souza; Figueiredo Filho, Altamir Oliveira de (Revista Uningá, 2022)
With the loss of dental elements and subsequent bone resorption, the rehabilitation process in an atrophic maxilla becomes a challenge for professionals. Alternatives such as autogenous, xenogeneic and allogeneic grafts, as well as alloplastic biomaterials, have been used for bone volume gain. The technique of lifting the maxillary sinus to the posterior region of the maxilla is well described in the literature and does not present major complications. Morphogenetic proteins (BMPs) appear as adjuvants in this technique and can replace grafts or be combined with them. The objective of this study was to present the use of different materials for the reconstruction of the atrophic maxilla in order to give back to a patient the bone contour and volume she had lost. The reported case shows the employment of recombinant human bone morphogenetic protein 2 (rhBMP-2), associated with a particulate xenogeneic graft. The atrophic maxilla was reconstructed, and the indications, contraindications and possible limitations of the technique were discussed. It is possible to conclude that the technique used was satisfactory, the patient evolved well and is awaiting installation of an implant-supported prosthesis.